Reading Difficulties of Grade One Learners in Mother Tongue Based- Multi-lingual Education (MTB-MLE) in Relation to Performance: Basis for Intervention Plan - Pesales, Phoebe Mae Rose P.; Apohen, Sharon L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the reading difficulties encountered by Grade One learners in District 1 of the Schools Division of Bago City for the school year 2023-2024 and examines their impact on academic per-formance. Utilizing a descriptive-correlational research design, the study assessed 231 Grade One learners from five elementary schools using a modified Reading Difficulty Checklist. Findings indicate that learners experience moderate difficulties across five key areas of reading: phonemic awareness, phonics, fluency, vocabulary, and com-prehension, with comprehension posing the greatest challenge. The study also reveals that demographic factors such as age, sex, parents’ educational attainment, and family income significantly influence reading proficiency. Additionally, a strong correlation was found be-tween reading difficulties and academic performance, highlighting the need for targeted intervention programs. Based on the results, an in-tervention plan is proposed to enhance reading skills and improve academic outcomes for young learners.